Structural, mechanical, and thermal properties of Mo2MB2 (M = Ti, Zr and Hf) super-alloys from first-principles approach - Job W. Wafula; George S. Manyali (Next Materials)
The mechanical strength of Nickel-based super-alloys decreases as temperature increases beyond 1423 K, rendering them unsuitable for ultra-high-temperature applications. Mo-based alloys exhibit high melting points however, they undergo rapid oxidation and creep at high temperatures. Borides have strong refractory metal phase hence improved oxidation resistance and mechanical stability. For instance, molybdenum-based borides, like Mo-Zr-B and Mo-Hf-B super-alloys, have demonstrated electronic and thermodynamic stability in earlier studies, but their complete set of elastic tensors has not been published. Moreover, Mo2TiB2’s mechanical, thermal, and structural properties have not yet been studied. The structural, mechanical, and thermal properties of Mo2TiB2, Mo2ZrB2, and Mo2HfB2 super-alloys were determined in this study using first-principles calculations performed utilizing the Quantum ESPRESSO package. Mo2ZrB2 and Mo2HfB2 super-alloy equilibrium lattice constants are in agreement with previous theoretical data. All three alloys were found to be mechanically stable when their calculated elastic constants satisfied the Born-Huang mechanical stability requirements. The Mo2TiB2 appears to be hard, with a Vicker’s hardness greater than 20 GPa. In general, Mo2TiB2, Mo2ZrB2, and Mo2HfB2 super-alloys’ exceptional mechanical properties imply that they are suitable for structural applications in high temperature environments, including high-performance automotive parts, protective coatings, and aerospace propulsion systems.